1999
DOI: 10.1210/endo.140.2.6500
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Action of 17β-Estradiol on Kainate-Induced Currents in Hippocampal Neurons Lacking Intracellular Estrogen Receptors*

Abstract: 17Beta-estradiol can potentiate kainate-induced currents in isolated hippocampal CA1 neurons. The action of estrogen was rapid in onset, steroid and stereospecific, and reversible. The potentiation could be mimicked by 8-bromo-cAMP, an activator of protein kinase A. As the hippocampus expresses both isoforms of the intracellular estrogen receptor (ER alpha and ER beta), the role of ERs in the rapid action of 17beta-estradiol remains elusive. Here we report that the rapid action of 17beta-estradiol is independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(70 citation statements)
references
References 29 publications
1
67
0
2
Order By: Relevance
“…However, using knockout mice that do not express ERs is another approach that can be utilized to determine if ERs are integral for E 2 's functional effects. In support, E 2 rapidly increases kainate-induced currents in the hippocampus of ER knockout mice [40]. Moreover, some of these studies by Moss and colleagues demonstrated that an ER antagonist, ICI182,780, when applied to the hippocampus did not attenuate effects of E 2 .…”
Section: Rapid And/or Membrane Actions In the Hippocampus For E 2 'S mentioning
confidence: 94%
“…However, using knockout mice that do not express ERs is another approach that can be utilized to determine if ERs are integral for E 2 's functional effects. In support, E 2 rapidly increases kainate-induced currents in the hippocampus of ER knockout mice [40]. Moreover, some of these studies by Moss and colleagues demonstrated that an ER antagonist, ICI182,780, when applied to the hippocampus did not attenuate effects of E 2 .…”
Section: Rapid And/or Membrane Actions In the Hippocampus For E 2 'S mentioning
confidence: 94%
“…This belief stems primarily from the fact that many of the rapid effects of E2 can be induced by selective ERα or ERβ ligands, antagonized by the ER antagonist, ICI 182,780, or are lost in animals bearing mutations in ERα and/or ERβ genes (Couse and Korach, 1999, Singer et al, 1999, Dubal et al, 2001, Wade et al, 2001, Abraham et al, 2003, Boulware et al, 2005. Another view is that estrogen activates a unique membrane ER (mER) (Gu et al, 1999, Toran-Allerand, 2004, Toran-Allerand, 2005, Qiu et al, 2006b). …”
Section: Membrane-initiated Signaling Of E2mentioning
confidence: 99%
“…Based on the findings from the hippocampal slice, it was hypothesized that E2 activates a Gs-coupled receptor on the extracellular surface of hippocampal neurons, which operates in concert with an internal action of E2 on cAMP-dependent phosphorylation (Gu and Moss, 1998). Importantly, these rapid actions of E2 on kainate-induced currents in hippocampal neurons are suggesting a novel mechanism (receptor) for the rapid actions of E2 in the hippocampus (Gu et al, 1999). In addition E2 and E2-BSA, when applied acutely to the hippocampus in ovariectomized animals, produce a sustained reduction of the slow I AHP in CA1 pyramidal neurons (Carrer et al, 2003).…”
Section: Membrane-initiated Signaling Of E2mentioning
confidence: 99%
“…Такі симптоми можуть бути викликані прискореним розвитком інволю-тивних форм остеартрозу і остеохондрозу в результаті дегенеративно-дистрофічних процесів у сполучнотканинних утвореннях (зв'язковий апарат, міжхребцеві диски), а також розвитком системного остеопоро-зу, що проходять більш прискорено на тлі дефіциту естрогенів [1,2]. Має особливе значення і модулювальний вплив жіночих статевих гормонів на центральну нервову систему, зокрема -ноцицептивну чутливість [3] через дію на глутаматіндуковані струми, інгібування рецепторів ГАМК і гліцину, або модуляції опіоїдних рецепторів у задніх ро-гах спинного мозку [4,5,6], що також може впливати на виникнення больових симптомів у м'язах і суглобах в постменопаузі. Основ-на дія естрогену на нейрони здійснюється через активацію ядерних α-і β-рецепторів естрогену (ERα/β), що викликає довгостро-кові геномні ефекти [7], а також активацію цитоплазматичних механізмів сигналізації поблизу плазматичної мембрани або на її поверхні [8] і здійснюється через мембранні класичні ERs [9] та новостворені ERs [10].…”
Section: вступunclassified
“…Відомо, що естроген потенціює глута-матіндуковані струми через вплив на процес цАМФ-залежного фосфорилювання [4], а селективний антагоніст ERα пресинаптично полегшує збуджувальну синаптичну переда чу до нейронів желатинозної субстанції. У цих умовах посилюється пресинаптичне галь-мування первинних аферентів гальмівними нейронами желатинозної субстанції [12].…”
Section: результати та їх обговоренняunclassified